Dog Fighting as a More Serious Form of the Crime of Animal Cruelty - Batrićević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
There is no doubt that dog fighting represents a form of extreme animal cruelty. This "bloody sport" is also considered a serious and complex social and legal phenomenon, whose significance goes beyond the frames of the animal welfare issue. Criminal offence comprised of killing and torture (now: abuse) of animals was included in the criminal legislation of the Republic of Serbia in 2006. However, its more serious form, dealing with animal fights, became a part of our criminal law in 2009, after alterations and amendments of the Criminal Code. In the same year, our country adopted its first Law on Animal Welfare, causing certain acts that are either directly or indirectly connected to animal fighting to be proclaimed as misdemeanours. The social hazard of dog fights, the link between them and other violent criminal activities and the awareness of the significance of animal welfare in contemporary society require efficient enforcement of the above mentioned laws. The aim of this paper is to analyze relevant legal provisions as well as to attempt to solve the difficulties that might occur during their enforcement.